Cooperación internacional en la lucha contra el terrorismo - Lim, Su Jin; Palomo Garrido, Aleksandro (Nómadas. Critical Journal of Social and Juridical Science, 2017)
One point about international cooperation has become relevant in the last years. It is international cooperation in the fight against terrorism. This fight against terrorism has become increasingly important on the international agenda. It is necessary to analyze how this international cooperation is being developed.
Keywords: International cooperation; security; terrorism.